Distinct iPS Cells Show Different Cardiac Differentiation Efficiency. (27th October 2013) - Ohno, Yohei; Yuasa, Shinsuke; Egashira, Toru; Seki, Tomohisa; Hashimoto, Hisayuki; Tohyama, Shugo; Saito, Yuki; Kunitomi, Akira; Shimoji, Kenichiro; Onizuka, Takeshi; Kageyama, Toshimi; Yae, Kojiro; et al.
Abstract : Patient-specific induced pluripotent stem (iPS) cells can be generated by introducing transcription factors that are highly expressed in embryonic stem (ES) cells into somatic cells. This opens up new possibilities for cell transplantation-based regenerative medicine by overcoming the ethical issues and immunological problems associated with ES cells. Despite the development of various methods for the generation of iPS cells that have resulted in increased efficiency, safety, and general versatility, it remains unknown which types of iPS cells are suitable for clinical use. Therefore, the aims of the present study were to assess (1) the differentiation potential, time course, and efficiency of different types of iPS cell lines to differentiate into cardiomyocytes in vitro and (2) the properties of the iPS cell-derived cardiomyocytes. We found that high-quality iPS cells exhibited better cardiomyocyte differentiation in terms of the time course and efficiency of differentiation than low-quality iPS cells, which hardly ever differentiated into cardiomyocytes. Because of the different properties of the various iPS cell lines such as cardiac differentiation efficiency and potential safety hazards, newly established iPS cell lines must be characterized prior to their use in cardiac regenerative medicine.